DYNAMICS OF INTERPERSONAL COMMUNICATION IN IMPROVING TEAMWORK EFFICIENCY - Indah Sulistiani; Syarifuddin; Selly Sipakoly (Jurnal Komunikasi, 2024)
In an organizational environment, if there is increased interpersonal communication, it will have a positive impact on the level of commitment to the organization. By involving an effective communication process, all tasks within an organization can be carried out well. A collection of people working together to accomplish a task or reach a common goal is known as a team. In teamwork, each member brings unique expertise, experience, and skills that contribute to achieving the team's goals. Communication, cooperation, coordination, and mutual support among team members are important aspects of an effective work team. Through cooperation and synergy, work teams can increase efficiency, productivity and quality of work. This article's methodology makes use of literature study, which is a technique for gathering data that entails comprehending and examining theories from a variety of research-related books. The ideas of interpersonal communication, cooperation, and effectiveness in collaboration are covered in this study, as well as the connection between the two